Pathway-specific dopaminergic deficits in a mouse model of Angelman syndrome - Thorfinn T. Riday; Elyse C. Dankoski; Michael C. Krouse; Eric W. Fish; Paul L. Walsh; Ji Eun Han; Clyde W. Hodge; R. Mark Wightman; Benjamin D. Philpot; C.J. Malanga (The Journal of Clinical Investigation, 2012)
Angelman syndrome (AS) is a neurodevelopmental disorder caused by maternal deletions or mutations of the ubiquitin ligase E3A (UBE3A) allele and characterized by minimal verbal communication, seizures, and disorders of voluntary movement. Previous studies have suggested that abnormal dopamine neurotransmission may underlie some of these deficits, but no effective treatment currently exists for the core features of AS. A clinical trial of levodopa (l-DOPA) in AS is ongoing, although the underlying rationale for this treatment strategy has not yet been thoroughly examined in preclinical models. We found that AS model mice lacking maternal Ube3a (Ube3am–/p+ mice) exhibit behavioral deficits that correlated with abnormal dopamine signaling. These deficits were not due to loss of dopaminergic neurons or impaired dopamine synthesis. Unexpectedly, Ube3am–/p+ mice exhibited increased dopamine release in the mesolimbic pathway while also exhibiting a decrease in dopamine release in the nigrostriatal pathway, as measured with fast-scan cyclic voltammetry. These findings demonstrate the complex effects of UBE3A loss on dopamine signaling in subcortical motor pathways that may inform ongoing clinical trials of l-DOPA therapy in patients with AS.